THE POSSIBILITIES OF ETIOTROPIC AND SYMPTOMATIC TREATMENT IN THERAPY AND PROPHYLAXIS OF DIFFERENT FORMS OF LARYNGITIS IN CHILDREN WITH ACUTE RESPIRATORY INFECTIONS - N. Yu. Radtsig; N. V. Ermilova; E. P. Sel'kova (Вопросы современной педиатрии, 2012)
The article deals with the problem of prevalence, treatment and prophylaxis of inflammatory disorders of the larynx in patients with acute respiratory infections. The authors show their own data on the occurrence of different forms of laryngitis in children. The role of endoscopy in diagnostics of this condition is described. In order to reveal the cause of obstructive laryngitis recurrence virological and endoscopic examination was performed in 100 patients who had had recurrent/relapsing croup. The shown data are over 2 epidemic seasons. The principles of patients management are described, the data on clinical efficacy of treatment and prophylaxis schemes, including complex homeopathic drugs, are represented. The authors made conclusions, that prevalence of different forms of laryngitis against the background of acute respiratory infections is 3,91-29% (among the group of frequently ill children). Children with recurrent /relapsing laryngitis (including obstructive variants) accounts for 53,32%. No correlation between amount of pathogens, episodes of obstructive laryngitis and organic pathology of the larynx in children with recurrent/relapsing laryngitis were found. Taking into account the diversity and variability of the causative agents, it is reasonable to include the drugs with antiviral activity, high efficacy and safety into the schemes of treatment of such patients, as well during prolong treatment.